Becoming Permanent: The Transition Characteristics of Temporary Foreign Workers to Permanent Residents in Canada. (8th July 2020) - Haan, Michael; Yoshida, Yoko; Amoyaw, Jonathan; Iciaszczyk, Natalie
Abstract: In recent years, Canada has been not only welcoming growing numbers of temporary foreign workers (TFWs), but also, increasingly, creating pathways that allow workers and their families to become permanent residents. In this paper, we use a series of unique longitudinal files to study the factors that predict a TFW's transition to permanence. We find that age, sex, skill level and duration as a temporary resident are all important factors for understanding who obtains legal residency in Canada, but that source country wealth is not. We discuss the implications of our findings and make suggestions for future research.